Astrobiology, History, and Society Life Beyond Earth and the Impact of Discovery - Vakoch, Douglas A. (Advances in Astrobiology and Biogeophysics, 2013)
This book addresses important current and historical topics in astrobiology and the search for life beyond Earth, including the search for extraterrestrial intelligence (SETI). The first section covers the plurality of worlds debate from antiquity through the nineteenth century, while section two covers the extraterrestrial life debate from the twentieth century to the present. The final section examines the societal impact of discovering life beyond Earth, including both cultural and religious dimensions. Throughout the book, authors draw links between their own chapters and those of other contributors, emphasizing the interconnections between the various strands of the history and societal impact of the search for extraterrestrial life. The chapters are all written by internationally recognized experts and are carefully edited by Douglas Vakoch, professor of clinical psychology at the California Institute of Integral Studies and Director of Interstellar Message Composition at the SETI Institute. This interdisciplinary book will benefit everybody trying to understand the meaning of astrobiology and SETI for our human society.